Sagnac Gyroscopes and the GINGER Project - Di Virgilio, Angela D. V. (Frontiers in Astronomy and Space Sciences, 2020)
Large-frame optical Sagnac gyroscopes, more commonly called ring laser gyroscopes, are considered the only device able to provide fast and very high sensitivity measurement of the length of the day (LOD) and of the Earth rotation axis variations. Several large-frame Sagnac gyros are presently operative with a high duty cycle and a sensitivity well below fractions of nrad/s in 1 s measurement. At present, other inertial angular rotation sensors are not competitive with ring laser gyroscopes. The feasibility depends on the so-called hetero-lithic ring lasers. The present state of the art is reported and the feasibility of the main goals for geodesy discussed.